Greely Relief Expedition : reception of Lieut. A. W. Greely, U.S.A., and his comrades, and of the Arctic relief expedition, at Portsmouth, N.H., on August 1 and 4, 1884 - McGinley, William Anderson, 1831-1896.; United States. Navy Department. (Washington : G.P.O., 1884)
Mode of access: Internet.